2012
DOI: 10.1007/s10071-012-0568-9
|View full text |Cite
|
Sign up to set email alerts
|

Contagious yawning in domestic dog puppies (Canis lupus familiaris): the effect of ontogeny and emotional closeness on low-level imitation in dogs

Abstract: Contagious yawning is a well-documented phenomenon in humans and has recently attracted much attention from developmental and comparative sciences. The function, development and underlying mechanisms of the phenomenon, however, remain largely unclear. Contagious yawning has been demonstrated in dogs and several non-human primate species, and theoretically and empirically associated with empathy in humans and non-human primates. Evidence of emotional closeness modulating contagious yawning in dogs has, nonethel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 43 publications
3
71
1
2
Order By: Relevance
“…Therefore, though these children may have yawned in response to a yawning clip, this only occurred after a control clip had already occurred. Different latency periods for contagious yawning have also been found in dogs-younger dogs typically have longer latency periods than do older dogs [10]. Future research can make use of order effects testing to see whether contagious yawns after control clips are indeed due to longer latency periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, though these children may have yawned in response to a yawning clip, this only occurred after a control clip had already occurred. Different latency periods for contagious yawning have also been found in dogs-younger dogs typically have longer latency periods than do older dogs [10]. Future research can make use of order effects testing to see whether contagious yawns after control clips are indeed due to longer latency periods.…”
Section: Discussionmentioning
confidence: 99%
“…A developmental trajectory for contagious yawning has also been observed in dogs. A recent study reported that dogs only start to yawn contagiously around 7 months of age [10]. Similarly, infant chimpanzees seem to show less susceptibility to yawn contagion than adult chimpanzees [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are now studies of empathy in mammals, from mice (Mus musculus) [2], rats (Rattus norvegicus) [3] and dogs (Canis lupus familiaris) [4] to elephants (Loxodonta africana) [5], and also in birds [6,7]. One common behavioural measure is contagious yawning (CY), which appears to fit the empathy framework because of four key findings: (i) human adults high on other measures of empathy show more CY [8]; (ii) humans with developmental and personality disorders in which empathy is impaired show diminished CY [8][9][10][11]; (iii) CY is positively biased by familiarity in humans (Homo sapiens) [12], chimpanzees (Pan troglodytes) [13], bonobos (Pan paniscus) [14], gelada baboons (Theropithecus gelada) [15] and dogs [16][17][18], as is typical of other measures of empathy; and (iv) presented with a variety of body movements apes exclusively increase yawning in response to observed yawning, suggesting CY's high specificity [19,20]. Aiding this specificity, brain areas associated with the human mirror neuron system activate in humans viewing yawns [21][22][23], with mirror neurons having been implied as a proximate neural mechanism for empathy [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Human psychology regards emotional contagion as a fundamental part of human sociality and cognition essential for developing "mind-reading" skills (e.g., Hatfield, Rapson, & Le, 2009) -making it of great interest whether, and in what forms, emotional contagion occurs in non-human animals. Some studies on mammals hint this direction: a study on contagious yawning in dog pups (Canis lupus familiaris) found that several subjects got sleepy during the yawning sessions (Madsen & Persson, 2013). Studies on orangutans (Pongo pygmaeus) and geladas (Theropithecus gelada) have revealed rapid facial mimicry in play activities, something thought to suggest emotional contagion (Mancini, Ferrari, & Palagi, 2013;Ross, Menzler, & Zimmerman, 2008).…”
mentioning
confidence: 99%